Bringing Children Back to School: Perspectives from Education Policies and Child Labour Laws - Sangai, Ajey (JOURNAL OF INDIAN EDUCATION, 2008)
If education is to be considered as a capability, then child labour, which either forces the children to quit the schooling or keeps them away from schools, leads to capability deprivation rendering the out of school children as impoverished. The paper presents the need for widening the definition of ‘child labour’ in consonance with Article 32 of the Convention on the Rights of Children, 1989 to include children who though are not employed in any hazardous occupations or perform any activities listed under Schedule 1 of the Child Labour (Protection and Regulation) Act, 1986 yet are denied education. The paper also argues for vocational, life-skill and craft-based education in elementary level so as to create interest in education besides equipping the schools with basic facilities and creating a healthy environment for approaching ‘disinterest in studies’ as a cause for huge number of children being ‘out of school’.